THE IMPORTANCE OF IJTIHAD IN ISLAMIC LAW - Yudi surono, Lc., MHI (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2022)
The development and progress of the times both in the fields of science and technology is a necessity in human civilization. These advances on the one hand offer and have a positive impact on human life, namely the availability of various facilities that make it easy for humans to fulfill their needs. But on the other hand, these advances raise and give birth to various problems that are quite complex. If this problem is not responded to properly, it will cause instability, unrest and a threat to human life. Seeing this reality, if the applicable law is not able to answer the problems that are being faced by the community, while if these problems are left it will create a legal vacuum, this is in law not justified in the existence of a legal vacuum. Therefore, a judge is required to be able to fill the void, and must be able to make an accommodative legal solution, regulate all problems that arise in a fair manner and bring the common good. To answer this problem, an instrument has been found, namely ijtihad